A qualitative service evaluation of nurses’ satisfaction with care in wards implementing hourly nursing rounds - McNeil, Margaret (2011)
BACKGROUND: The delivery of safe quality patient care with attention to addressing basic care needs is pertinent to the current concerns about care within the National Health Service (NHS). The introduction of hourly nursing rounds is one way in which such concerns can be addressed. Hourly nursing rounds involve the nurse routinely visiting every patient every hour to address the immediate needs of the patient based on the 3P’s which involves, pain, potty (continence) and positioning. This concept was brought across from the United States of America, and is now being implemented in trusts across the United Kingdom. The researcher was given the opportunity to explore how well this system is working in practice within two large teaching hospitals in a particular NHS Trust. AIM OF THE STUDY: To evaluate nurses’ satisfaction with care on wards implementing hourly nursing rounds. METHODS: Service evaluation with a qualitative approach was utilised. Ten nurses from four wards across two hospitals within one NHS trust were interviewed regarding their experiences in carrying out the hourly nursing rounds. FINDINGS: Four main themes were identified from the interviews: improving quality of patient care, patient safety, challenging ritualistic care and resourcing. These themes are evident in the literature, some of which contradict what is said, whereas others support what is said. Nurses are divided in opinion as to whether they feel hourly nursing rounds have had an impact on improving the quality of patient care and enhancing patient safety. Challenges to carrying out the rounds were identified as difficulties due to time and staffing issues. Nurses expressed the sometimes unrealistic expectations to carry out the rounds on all patients every hour. However the rounds provide a structured proactive approach to anticipate patients’ immediate care needs. CONCLUSION: The generalisability of this small scale study is limited; however it does illustrate nurses’ experiences of carrying out the hourly nursing rounds. It identifies implications for nursing practice and recommendations for future research.